Effect of sintering temperature on microstructure of hydrothermally prepared bismuth sodium titanate ceramics - Pookmanee P. (2014)
Bismuth sodium titanate (Bi1/2Na1/2TiO3 or BNT) powders were prepared by the hydrothermal route with starting chemicals containing Bi(NO3)3.5H2O, NaNO3 and Ti[i-OPr]4 in a PTFE-lined autoclave. After hydrothermal treatment at 200 °C for 20 h, the powders were filtered and washed with deionized water until the pH of the washing solution was 10. After drying in an oven at 100 °C for 5 h, white powders of BNT were obtained. X-ray diffraction (XRD) patterns of BNT fine powders show that well developed crystallite with a pure perovskite phase have been formed. The powders were pressed into disc shape of 10 mm in diameter and 1.6 mm thick. The green bodies were sintered in close alumina crucible at 800, 900, 1000 and 1050 °C for 3 h, to obtain the highest density. The microstructure of the powders and ceramics were investigated by scanning electron microscopic (SEM) technique. © 2003 Elsevier Ltd. All rights reserved.